2019
DOI: 10.1002/ccr3.2477
|View full text |Cite
|
Sign up to set email alerts
|

A novel larynx‐preserving pharyngectomy technique using a thyroid gland flap after chemoradiotherapy

Abstract: This case report describes larynx-preserving pharyngectomy after chemoradiotherapy using a thyroid gland flap. A thyroid gland flap has good blood supply and reconstruction can be done in the same surgical field. The thyroid gland flap has potential as a novel appropriate flap for use in head and neck surgery. K E Y W O R D S arytenoid reconstruction, chemoradiotherapy, head and neck surgery, larynx-preserving pharyngectomy, thyroid gland flap How to cite this article: Ogawa T, Okamoto H, Inukai D, et al. A no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…The use of a TGF for glottic reconstruction after vertical laryngectomy was initially reported in 1990 by Kojima et al [9]. Since then, the effectiveness of a TGF has been demonstrated in larynx-preserving pharyngectomy and supracricoid partial laryngectomy after radiochemotherapy [6,10]. Furthermore, Ogawa et al [6] showed that a TGF with a sufficient blood supply prevents cervical infection and dehiscence.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The use of a TGF for glottic reconstruction after vertical laryngectomy was initially reported in 1990 by Kojima et al [9]. Since then, the effectiveness of a TGF has been demonstrated in larynx-preserving pharyngectomy and supracricoid partial laryngectomy after radiochemotherapy [6,10]. Furthermore, Ogawa et al [6] showed that a TGF with a sufficient blood supply prevents cervical infection and dehiscence.…”
Section: Discussionmentioning
confidence: 99%
“…Since then, the effectiveness of a TGF has been demonstrated in larynx-preserving pharyngectomy and supracricoid partial laryngectomy after radiochemotherapy [6,10]. Furthermore, Ogawa et al [6] showed that a TGF with a sufficient blood supply prevents cervical infection and dehiscence. We harvested a TGF from the superior aspect of the designated thyroid lobe.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The thyroid gland flaps were completely adapted to the neck defects and prevented leakage, thyroid cartilage infection, and necrosis even after high-intensity chemoradiotherapy. Particularly in the case of reconstruction for hypopharyngeal cancer, the arytenoid height reconstruction was constitutive, and this improved quality of life in terms of swallowing 15 (Fig. 10 ).…”
Section: Discussionmentioning
confidence: 99%
“…We therefore used this thyroid gland flap for salvage head and neck surgery. 13 15 The method uses the same surgical site and the flap can be raised by the head and neck surgeons themselves.…”
Section: Introductionmentioning
confidence: 99%